In Vitro Anti-Inflammatory Activity of Three Peptides Derived from the Byproduct of Rice Processing - Qu, Tingmin; He, Shuwen; Ni, Ce; Wu, Ying; Xu, Zhou; Chen, Mao-Long; Li, Honghui; Cheng, Yunhui; Wen, Li (Plant foods for human nutrition (Dordrecht), 2022)
Inflammation is a contributing factor to the initiation and progression of many diseases, and some food-derived biofunctional peptides show high anti-inflammatory activity. In our previous study, we demonstrated that peptides derived from trypsin hydrolysis of rice protein show good immunological activity. In the present study, proteins of broken rice were extracted and identified by macroporous resin fractionation and liquid chromatography/tandem mass spectrometry (LC-MS/MS). Subsequently, a bioinformatics prediction and in silico simulation approach was used to screen for peptides showing anti-inflammatory activity, including inhibition of the production of nitric oxide and proinflammatory cytokines (interleukin-1 β , interleukin-6, and tumor necrosis factor- α ) by lipopolysaccharide-stimulated RAW264.7 mice macrophages. Three peptides (DNIQGITKPAIR, IAFKTNPNSMVSHIAGK, and IGVAMDYSASSKR) that demonstrated the highest binding affinity were synthesized, and their in vitro anti-inflammatory activity was investigated. This is the first study that integrates LC-MS/MS identification and bioinformatics prediction for reporting the anti-inflammatory activity of anti-inflammatory peptides derived from broken rice protein. The study findings revealed that the peptides derived from the byproduct of rice milling could be potentially used as natural anti-inflammatory alternativities.